Acid pretreatment of support promotes Pd/SiO2 activity for formaldehyde oxidation at room temperature. Issue 21 (22nd September 2022) - Liu, Xiaofeng; Wang, Chunying; Li, Yaobin; He, Hong
Abstract : Hydroxyl groups on SiO2 produced by acid pretreatment favored the anchoring of Pd particles and increased their dispersion, which induced more oxygen vacancies on the surface of catalysts and further enhanced H2 O activation. Abstract : Formaldehyde (HCHO) is a major pollutant in indoor air. The development of low-cost and high-efficiency technologies to remove HCHO at room temperature is thus of great importance. Here, we developed a simple method involving acid pretreatment of SiO2 to improve a Pd/SiO2 (HNO3 )-R catalyst for HCHO oxidation. Multiple characterization results illustrated that the hydroxyl groups on SiO2 produced by the acid pretreatment favored the anchoring of Pd particles and increased their dispersion. The increase in Pd dispersion induced more oxygen vacancies on the surface of the Pd/SiO2 (HNO3 )-R catalyst because of the increased number of hydrogen spillover sites; this further enhanced H2 O activation to form surface-active hydroxyl groups, thus significantly increasing the intrinsic activity of the Pd/SiO2 (HNO3 )-R catalyst for HCHO oxidation.